A pilot scale study on the treatment of rare earth tailings (REEs) wastewater with low C/N ratio using microalgae photobioreactor. (15th February 2023) - Wang, Haiyu; Liu, Zhuochao; Cui, Dan; Liu, Yuanqi; Yang, Liming; Chen, Houxing; Qiu, Genping; Geng, Yanni; Xiong, Zhensheng; Shao, Penghui; Luo, Xubiao
Abstract: Microalgae appear to be a promising and ecologically safe way for nutrients removal from rare earth tailings (REEs) wastewater with CO2 fixation and added benefits of resource recovery and recycling. In this study, a pilot scale (50 L) co-flocculating microalgae photobioreactor (Ma-PBR) as constructed and operated for 140 days to treat REEs wastewater with low C/N ratio of 0.51–0.56. The removal rate of ammonia nitrogen (NH4 + -N) reached 88.04% and the effluent residual concentration was as low as 9.91 mg/L that have met the Emission Standards of Pollutants from Rare Earths Industry (GB 26451–2011). Timely supplementation of trace elements was necessary to maintain the activity of microalgae and then prolonged the operation time. The dominant phyla in co-flocculating microalgae was Chlorophyta, the relative abundance of which was higher than 80%. Tetradesmus belonging to Chlorophyceae was the dominant genus with relative abundance of 80.35% . The results provided a practical support for the scaling-up of Ma-PBR to treat REEs wastewater. Graphical abstract: Image 1 Highlights: High NH4 + -N removal of 88.04% was achieved by microalgae in pilot scale. Reactor operated steadily for 140 days with effluent NH4 + -N below 10 mg/L. Timely pH adjustment and trace element addition are two key affect factors.